Risk factors for falls in patients with total hip arthroplasty and total knee arthroplasty: a systematic review and meta-analysis. Issue 7 (July 2019) - Lo, C.W.T.; Tsang, W.W.N.; Yan, C.H.; Lord, S.R.; Hill, K.D.; Wong, A.Y.L.
Summary: Objective: Falls are common after total hip arthroplasty (THA) and total knee arthroplasty (TKA). While previous studies have investigated various risk factors for falls in patients following THA and TKA, no systematic reviews have summarized these risk factors. Therefore, the current systematic review aimed to summarize evidence regarding risk factors for falls in patients after THA and/or TKA. Methods: MEDLINE, EMBASE, CINAHL, SPORTDiscus, and Physiotherapy Evidence Database (from inception to June 30, 2018) were searched. The methodological quality and quality of evidence of the included studies were assessed by two independent reviewers. Relevant data regarding participants' characteristics, study design, follow-up time points, and identified risk factors were extracted. Meta-analyses and narrative syntheses were performed. Results: Twelve studies with a total of 1, 292, 689 participants were included. Twenty-nine identified risk factors for post-THA/TKA falls were classified into either inpatient or post-discharge risk factors. Key risk factors for both post-THA and/or post-TKA inpatient falls that showed moderate level of evidence included: postoperative complications or comorbidities and revision THA/TKA. Likewise, risk factors for post-discharge falls after THA and/or TKA that demonstrated moderate level of evidence included: medications, psychiatric diseases, living alone, prior history of TKA, falls history and female gender. The quality of the included studies varied and sample sizes were not justified. Conclusions: This review summarized both non-modifiable and modifiable risk factors for post-THA/TKA falls. Our findings highlight the importance of developing strategies to lower the falls risk among patients following THA/TKA.